A Bandpass Filter Based on Half Mode Substrate Integrated Waveguide-to-Defected Ground Structure Cells - Yong Mao Huang; Zhenhai Shao; Zhaosheng He; Chang Jiang You; Di Jiang (International Journal of Antennas and Propagation)
A half mode substrate integrated waveguide-to-defected ground structure (HMSIW-DGS) cell and its embedded form are proposed to miniaturize a bandpass filter. Both cells can purchase wideband frequency response and low insertion loss, as well as simple and easy fabrication. By cascading two of them according to design requirement, an X-band bandpass filter is designed and measured to meet compact size, low insertion loss, good return loss, second harmonic suppression, and linear phase.